(untitled) (Baghdad Science Journal, 2025)
Some biological aspects of the zebra mussel, Dreissena polymorpha have been studied at Al-Musayab thermal power plant ,sixty km. south west of Baghdad. Data collected during the period extended from November, 2002 to October, 2003 except for the month of April The population consisted of five age groups; O, I, II, III, and IV which have 0, 1, 2, 3 and 4 annuli respectively. The study also proved the validity of annuli readings for age and growth determination. The average annual growth rates for age groups O,I, II, III, and IV were 5.7, 5.5, 5.4, 5.2 and 5.4 respectively. Average calculated length for laboratory reared mussel was 2.5 mm compared to 5.4 mm in natural environment. Correlation coefficients were very high between age and shell length, shell hight and total weight. their respective values were 0.892, 0.929 and0.934. Mature gonads were recognized during March, June and October where sex ratio was determined. Chi-square test showed no statistical difference between the two sexes.By calculating total average weights during months of study, two maturing and spawning periods were noted. The first was in late June and July, the second extended from September through February.